Interculturality, perspectives in the Latin American context - Valencia Salazar, Edilberto (2021)
The purpose of this article is to reflect on interculturality as an emerging issue in modernity, postmodernity and its scope, in the current political system, in the Latin American context. From the analysis made and ideas presented, it is shown that, if intercultural public policies continue to be developed in the current capitalist system, it will not be possible to develop theplanned objectives because, the neoliberal system, is generating legal forms capable of distorting the true value of the cultural elements of the original peoples (tourist goods or cultural heritage of humanity). Interculturality must be one of the public policies with the highest priority emphasis in the field of education for the 21st century and must be based on; learn to do, learn to know, learn to live together and learn to be, with more importance in learning to do, that is, every individual must know how to do, what he learned and developed in a university. If this  does not happen then the university system will have failed and, above all, those who instruct it. We believe that functional interculturality is contaminated because it was developed by and for the current neoliberal state. Rather, it should be considered an objective interculturality without ideologies that allows decolonizing the power of being and knowing knowledge. One of the ways of going under, fertilizing and preparing the ground for the establishment of a new political and social system, is by generating political parties and social movements, capable of incorporating interculturality as a structural element to assume power. And develop inclusive leadership.